Effect of Pressure on Carbon monoxide Oxidation on Titania Supported Platinum Nanoparticles Catalyst - Jovine Emmanuel (East African Journal of Biophysical and Computational Sciences)
Thermographic testing methodology was developed to facilitate measurements of particle dimension and substrate influence in heterogeneous catalysts. A screening chip with several areas of less stress silicon nitride membranes which displays less heat conductivity and heat capacity was used. Heat produced during the reaction on catalysts deposited on membranes was established through IR camera which gave the value of the turn over frequency. Effect of pressure on CO conversion on titania supported Pt particles of different dimension was measured on 120 catalysts concurrently. The reaction was studied at various O2 and CO pressures at 170 ℃ and 240 ℃. At these temperature conditions, activity increased with increase of O2 and CO pressure, in agreement with previous reports.